Phytotoxicity of cobalt ions on the duckweed Lemna minor – Morphology, ion uptake, and starch accumulation. (July 2015) - Sree, K. Sowjanya; Keresztes, Áron; Mueller-Roeber, Bernd; Brandt, Ronny; Eberius, Matthias; Fischer, Wolfgang; Appenroth, Klaus-J.
Highlights: Uptake of Co 2+ does not inhibit iron uptake in L. minor. Co 2+ toxicity is independent of iron stress providing an unique test system. Plant growth but not photosynthesis was inhibited after 4 d of Co 2+ treatment. After this period surplus carbohydrate was stored as starch. Longer treatment decreased photosynthetic efficiency and reduced starch content. Abstract: Cobalt (Co 2+ ) inhibits vegetative growth of Lemna minor gradually from 1 μM to 100 μM. Fronds accumulated up to 21 mg Co 2+ g − 1 dry weight at 10 μM external Co 2+ indicating hyperaccumulation. Interestingly, accumulation of Co 2+ did not decrease the iron (Fe) content in fronds, highlighting L. minor as a suitable system for studying effects of Co 2+ undisturbed by Fe deficiency symptoms unlike most other plants. Digital image analysis revealed the size distribution of fronds after Co 2+ treatment and also a reduction in pigmentation of newly formed daughter fronds unlike the mother fronds during the 7-day treatment. Neither chlorophyll nor photosystem II fluorescence changed significantly during the initial 4 d, indicating effective photosynthesis. During the later phase of the 7-day treatment, however, chlorophyll content and photosynthetic efficiency decreased in the Co 2+ -treated daughter fronds, indicating that Co 2+ inhibits the biosynthesis of chlorophyll rather than leading to the destruction of pre-existing pigment molecules. In addition, during the first 4 d of Co 2+ treatment starch accumulated in the fronds and led to the transition of chloroplasts to chloro-amyloplasts and amylo-chloroplasts, while starch levels strongly decreased thereafter.